Logic-based program synthesis and transformation 20th International Symposium, LOPSTR 2010, Hagenberg, Austria, July 23-25, 2010, Revised Selected Papers - LOPSTR (Symposium) 2010 Hagenberg, Austria); Alpuente, Maria; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book constitutes the thoroughly refereed post-proceedings of the 20th International Symposium on Logic-Based Program Synthesis and Transformation, LOPSTR 2010, held in Hagenberg, Austria in July 2010. The 13 revised full papers presented together with two invited papers were carefully reviewed and selected from 26 submissions. Among the topics covered are specification, synthesis, verification, analysis, optimization, specialization, security, certification, application and tools, program/model manipulation, and transformation techniques for any programming language paradigm.
Electronic reproduction.
Keywords: Logic programming -- Congresses; Computer programming -- Congresses; Electronic books